THE EFFECT OF WORK LIFE BALANCE AND EMPLOYEE ENGAGEMENT ON EMPLOYEE PERFORMANCE AT PT IMA MONTAZ SEJAHTERA, LHOKSEUMAWE CITY - Putri Balqis; Nurmala; Yanita; Likdanawati (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to determine the effect of Work Life Balance and Employee Engagement on employee performance at PT Ima Montaz Sejahtera. The background of this study is based on the importance of balance between work life and personal life of employees and employee engagement to the company in increasing productivity and work results. The research method used is quantitative with an associative approach, where data is obtained by distributing questionnaires to the entire employee population with a saturated sampling technique. Data analysis was carried out using validity tests, reliability, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²) with the help of SPSS software. The results show that the Work Life Balance variable has a positive and significant effect on employee performance. Similarly, the Employee Engagement variable has a positive and significant effect on employee performance. Simultaneously, both variables have a significant positive effect on employee performance at PT Ima Montaz Sejahtera. Thus, companies need to maintain the balance between work and personal life of employees and increase their involvement in work to achieve optimal performance.